Ночевала тучка золотая: [повесть] / Анатолий Приставкин - Приставкин Анатолий Игнатьевич (День Победы, 2015)
Экземпляры: ДБ (20220929) / Инвентарный номер: 41419 / Цена: / Сис.шифр: 84 (2 Рос=Рус)6-4 / Авт.знак: П 77 / ГРНТИ: 17.82.31 / ББК: 84 (2 Рос=Рус)6-4